2020
DOI: 10.4028/www.scientific.net/msf.1010.584
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Biological Hydroxyapatite from Tuna Fish Bone for Biomedical Applications

Abstract: Natural hydroxyapatite (HAp) is known for its common use in biomedical applications including in orthopaedic and implantation. HAp can be extracted from natural resources such as eggshells, fish bones and coral. Annually, it is found that huge amount of tuna fish bones were thrown away and being wasted as results from great consumption of tuna fish. In this study, tuna fish bones were extracted and characterised to be used in biomedical applications. Specifically, tuna fish bones were cleaned, and calcined at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…EDS analysis was performed to evaluate the presence of trace elements, such as Ca and P, belonging to the isolated CHA and commercial HA, and the results showed a Ca/P weight ratio of 1.96 and1.578 for CHA and HA, respectively (Figure 3), indicating that the extraction process (alkaline hydrolysis) of CHA has affected the Ca/P ratio. However, according to previous studies, the Ca/P ratios of both CHA and HA are not significantly different, and they were within the accepted range for hydroxyapatite [39].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…EDS analysis was performed to evaluate the presence of trace elements, such as Ca and P, belonging to the isolated CHA and commercial HA, and the results showed a Ca/P weight ratio of 1.96 and1.578 for CHA and HA, respectively (Figure 3), indicating that the extraction process (alkaline hydrolysis) of CHA has affected the Ca/P ratio. However, according to previous studies, the Ca/P ratios of both CHA and HA are not significantly different, and they were within the accepted range for hydroxyapatite [39].…”
Section: Discussionsupporting
confidence: 76%
“…According to previous studies, the HA derived from fish bones shows improved biocompatibility and osteogenic differentiation activity, and enhanced potential for bone formation on scaffolds fabricated with HA. Thus, CHA is a potential biomaterial that can be employed with various synthetic or natural polymers to fabricate tissue-engineered bone substitutes for bone tissue regeneration applications [39]. XRD, FTIR spectroscopy, and EDS analyses of isolated CHA and commercially available HA were performed to compare and determine the crystallinity, chemical composition, and atomic percentage, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, higher yield (approximately 90%) of bone recovery from hoki frame treated by crude enzyme from mackerel intestine for 6 h at optimal conditions in comparison with other proteases was reported (Kim et al, 2003). Latif et al (2020) reported that biocalcium powder contains high calcium and phosphorus, especially calcium in the hydroxyapatite form (Ca 10 (PO 4 ) 6 (OH) 2 ). Hydroxyapatite was also considered be the same form of calcium-phosphate compound in the human bone (Benjakul et al, 2017(Benjakul et al, , 2018Latif et al, 2020).…”
Section: Yield Of Bio-calcium Powdermentioning
confidence: 99%
“…Latif et al (2020) reported that biocalcium powder contains high calcium and phosphorus, especially calcium in the hydroxyapatite form (Ca 10 (PO 4 ) 6 (OH) 2 ). Hydroxyapatite was also considered be the same form of calcium-phosphate compound in the human bone (Benjakul et al, 2017(Benjakul et al, , 2018Latif et al, 2020).…”
Section: Yield Of Bio-calcium Powdermentioning
confidence: 99%
“…Kongsri et al (2013); Panda et al (2014) extracted HAp from fish scales. Furthermore, Biazar et al (2020); Hasan et al (2020); Latif et al (2020); Surya et al (2021) used distinct varieties of fish bones to extract HAp using different methods. The routes most commonly used for the synthesis of HAp are sol–gel, precipitation, co‐precipitation, and hydrothermal (Malla et al, 2020).…”
Section: Introductionmentioning
confidence: 99%